The Linkage between Ecological Knowledge and Behaviour Intention in Green Campus Students - Idhun Prasetyo Riyadi; Baskoro Adi Prayitno; Puguh - Karyanto (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
The UI GreenMetric is a university world ranking for universities to assess and compare campus sustainability efforts. UI GreenMatric's ultimate goal is to assess how committed the universities are to environmental management in the campus area. Sebelas Maret University is ranked 76th in the world and 5th in the national level. Measurement of the ecological literacy ability of the students of Sebelas Maret University received low results on attitude and knowledge aspects. Measurement of attitude aspect using NEP scale got an average result equal to 62% while measurement of knowledge aspect using a scale of ecology concept gets an average result equal to 56%. This paper intends to discuss the relationship between attitude and knowledge aspects of students at Sebelas Maret University. Quantitative regression analysis is used to look at the relationship between the two aspects of ecological literacy on lecture activities and student attitude observation. Improved environmental management in the campus area can be done by improving the concept of students first because it can affect how students behave.